Foreign Policy of Russia: ‘Soft Power’ of the Regions - S. P. Arteev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
As relations between the Russian Federation and the West continue to deteriorate, traditional diplomatic instruments become less eff ective. Conversely, the role of alternative diplomatic channels is growing. However, the Russian foreign policy still tends to underestimate their potential. In particular, the soft power potential of the Russian regions appears to be largerly under-utilized. The paper starts with a general overview of the specifi c features of sub-state/sub-national actors in the world politics. In particular, the author emphasizes that these actors are synthetic by nature, which predetermines their particular role on the international scene, as they can use policy instruments specifi c to both state and non-state actors. The author provides a model for classifi cation of the Russian regions based on the level of their international activity. The paper examines by what means the international activities of the regions can infl uence the interstate relations and outlines two basic frameworks for joint actions of the federal center and the regions on the international arena: ‘culture and image-building’ and ‘political plus’. The author emphasizes the importance of the federal-regional cooperation in addressing foreign policy issues, particularly, in response to international crises. The paper assesses the capacity of diff erent Russian sub-national actors to actively participate through their soft power potential in normalization of interstate relations. The author concludes that this potential could be successfully integrated into the Russian foreign policy strategy. However, in order to improve the quality of the federal-regional cooperation on the foreign policy issues, it is necessary to develop a new framework for interaction between the federal center and the regions of the Russian Federation, based on greater involvement of regional representatives in the decision-making process (which implies reassessment of the entire system of federal relations).